Pengaruh Pengembangan Sumber Daya Manusia terhadap Kinerja Karyawan di Era New Normal pada Coffee Shop Di Kota Palembang - Thery Sania Zelika; Sabeli Aliya (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine the effect of human resource development on employee performance in the new normal era at a coffee shop in the city of Palembang. The method used in this study is a quantitative method, with a causal associative level of explanation. The sample used in this study were all coffee shop employees as many as 44 respondents. Collecting data by distributing questionnaires to coffee shop employees. Data analysis used simple linear regression. The results of the determination test in this study were 0.765. Means 76.5%, the distribution of employee performance variables can be explained by the variable of human resource development. The conclusion of this study shows that the development of human resources partially has a positive effect on employee performance at Return Space and Coffee Shop and Luthier Coffee in the new normal era.